The Study of Fouling Behavior for the Model Binary Mixture. Issue 1 (January 2021) - Gao, Shujuan; Liu, Xinsen; Zhang, Hu; Liu, Xuguo; Wang, Zhan; Wang, Xi
Abstract: This study systematically investigated the fouling behavior and mechanism of PAN Microfiltration (MF) membrane fouled with the model binary mixture (bovine serum albumin (BSA) and sodium alginate (SA)) of extracellular polymer substance (EPS) solution under different concentration and transmembrane pressure (TMP). The result showed that the fouling mechanism of the model binary mixture was the pore blocking and cake formation. Moreover, the SA plays a dominant role in the model binary mixture (BSA/SA). The higher SA concentration could cause the more serious membrane fouling (both the flux ( J ) and the available membrane area ( A / A0 ) decreased), and the total resistance increased and caused the fouling mechanism changing from combined complete blocking and cake filtration into individual cake filtration appeared earlier. In addition, increasing of the TMP can also aggravate membrane fouling and it could be accurately described by the cake-complete model. This studied offered insight into the model binary mixture in the fouling behavior and mechanism, which can be used as guidance for practical application.